Prediction of Sorghum Grain Yield Adopting Soil Water Balance Model - Rao, A Yogeshwar; latha, Y Padma; Rao, K Krishna (Annals of Arid Zone, 2016)
Eight years field study at Anantapur revealed that the grain yield of sorghum 'CSH5' varied widely between 450 and 2606 Kg/ha over the years. Soil water balance model developed by the Food and Agriculture Organisation was adopted and a close relationship between sorghum grain yield and the water used by the crop was established, accounting for 92 per cent (R2=O.92) of the year to year grain yield variations. The utility of the model in predicting crop yields and the ancillary data required to improve its validity are also discussed.